Ritelatur Review: Prosedur Pemeriksaan Coronary Angiogrhpy (Cag) Pada Kasus Acute Trasmular Myocardial Infraction - Muhammad Ridwan; Kusman Kusman (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Literature review: coronary angiography examination procedure in cases of acute trasmular myocardial infarction. Background: Acute transmural myocardial infarction (ATMI) is a critical condition that describes heart damage involving the entire thickness of the ventricular wall due to total blockage of the coronary arteries. This situation can cause serious complications such as heart failure, arrhythmia, and sudden death if not treated quickly. Coronary angiography has become an important diagnostic tool in the management of STEMI. This process allows the doctor to directly view the coronary arteries and determine the location and severity of the blockage. This knowledge is critical because it guides medical or surgical interventions that may be necessary to open blocked arteries and restore blood flow to the heart. Prompt use of coronary angiography, followed by interventions such as angioplasty and stent placement (percutaneous coronary intervention, PCI), has been shown to reduce heart damage, increase survival, and improve long-term outcomes for patients with STEMI. Method: This research is a literature review, where literature exploration is carried out in various databases with keywords such as Coronary Angiograhy, Cases of Acute Transmular Myocardial Infarction, etc. Reference sources used in preparing this article include Google Scholar, as well as articles in English and Indonesian scientific journals. Results: Coronary Angiography (CAG) examination in Acute Trasmular Myocardial Infarction (ATMI) cases involves patient preparation, equipment preparation, medical team, examination procedures, post-operative care, description of examination results, and its role in the management of AMTI. Patient preparation involves patient education about procedures, fasting before examination, renal function checks, medication adjustments, vascular access preparation, discussion of contrast agents, and vital monitoring. ATMI patients require special attention in this preparation. Equipment preparation includes a stable catheterization table, fluoroscopic imaging system, various types of catheters, appropriate contrast agents, resuscitation equipment, pre-procedure medication, and hemostasis equipment. The medical team involved in ATMI examination in ATMI patients involve interventional cardiologists, radiological technologists, catheterization nurses, catheterization technicians, and additional support personnel such as the anesthesia team and resuscitation team. The examination procedure includes patient preparation, vascular access, catheter insertion into the coronary arteries, evaluation and imaging of the coronary arteries, and completion of the procedure .Post-operative care includes hemodynamic monitoring, examination of the access site, gradual mobilization, hydration, monitoring reaction to contrast agent, patient education, and follow-up with a cardiologist. Examination results may show normal coronary arteries, narrowing of the arteries, complete blockage, formation of arteries collaterals, and left ventricular dysfunction. CAG examination has an important role in detecting coronary artery disease, pre-operative assessment, determining therapy, evaluating collaterals, and assessing left ventricular dysfunction in ATMI patients. CAG examination in ATMI patients requires careful preparation and involves collaboration a well-coordinated medical team to provide optimal results and a significant contribution in ATMI management. Conclusion: In the context of treating Acute Transmural Myocardial Infarction (MI), the Coronary Angiography (CAG) examination procedure has a central role in determining the diagnosis, evaluating the level of coronary artery damage, and guiding decision making regarding coronary intervention. CAG allows rapid and accurate diagnosis of MI by directly viewing the condition of the coronary arteries and assessing the degree of obstruction that could lead to myocardial infarction. CAG provides a detailed visual image of coronary artery damage, infarct size and the area of ??myocardial tissue affected, which is essential for planning optimal treatment strategy. CAG results assist the medical team in identifying coronary lesions that require immediate intervention, such as coronary angioplasty and stent placement, with the aim of restoring normal blood flow to the myocardial tissue. In addition to focusing on the affected coronary arteries, CAG also provides a comprehensive view on overall heart function and condition, helping to evaluate damage and risk of complications.